Management of chronic heart failure [Kronik kalp yetersizliǧinin yönetimi] - (:unkn) unknown (My University, 2007)
Heart failure is a chronic syndrome. This complex syndrome of symptoms, associated with significant morbidity and mortality, is the most common discharge diagnosis in patients over the age of 65. Management of heart failure needs a work by multidisciplinaries team with pharmacologic and nonpharmacologic sides. Generally in the heart failure management programs a doctor and a nurse who is in a corporation with him provide the communication between the other members of the team. Beside the multidisciplinaries team, a nurse performs care of the patient, training and also basic care applications. After, it is neccessary to make decisicion on training requirements of the patient. Training starts with the structure and function of the heart and it continues with the process and the causes of the disease. And later, it continues by teaching of management heart disease ( take to medicaments, resting, low salty diet, activity control of weight and oedema e.t.c), necessary abilities, kinds of the causes of heart failure and how can restrict them and also in which critical situation his doctor/nurse must be look for. It is explained influence and repercussion of medicaments and their usages. Patients with heart failure can survive in a good quality by learning symptoms and applications in the management of diseaes, the changes in the living styles and controlling the semptoms.